Environmental impact assessment of pavement road bases with reuse and recycling strategies: A comparative study on geopolymer stabilized macadam and conventional alternatives. (April 2021) - Zhang, Yiyuan; Gong, Hongren; Jiang, Xi; Lv, Xiuyuan; Xiao, Rui; Huang, Baoshan
Highlights: Geopolymer road base reduced global warming by 17.9% CO2 eq per function unit compared with cement stabilized macadam. Combined alkaline activator consisting of NaOH and water glass was suggested to be used from environment perspective. Use of NaOH had a great impact on ozone layer depletion. Application of geopolymer road bases caused a pollution transfer. Abstract: Geopolymer is a potential solution to the high carbon emissions caused by cement. Life cycle assessment (LCA) methodology was applied in this study to evaluate the environmental impacts of pavement road bases with reuse and recycling strategies. We considered four types of stabilized road base materials to evaluate environmental impacts: waste glass-fly ash based geopolymer stabilized macadam (WFAG), fly ash based geopolymer stabilized macadam (FAG), cement stabilized macadam (CS) and cement-fly ash stabilized macadam (CFAS). Two alkaline activators were used to synthesize geopolymer road base materials. The results showed that the application of geopolymer road bases reduced global warming (GWP) significantly. Comparing with CS, the GWP of WFAG and FAG declined by 17.9% CO2, eq per function unit. The combined alkaline activator consisting of sodium hydroxide (NaOH) and water glass had lower environmental impacts compared to the one with pure NaOH alkaline activator. The ozone layer depletion (ODP) of geopolymer stabilized road bases using pure NaOH solution was an order of magnitude higher than the ODP using the combined alkaline activator consisting of NaOH and water glass. For other indicators except GWP, the environmental impacts of conventional road bases were lower than geopolymer stabilized road bases, indicating a pollution transfer during application of geopolymer road bases.